Planned vaginal and planned cesarean delivery outcomes in pregnancies complicated with pregestational type 1 diabetes - A three-year academic tertiary hospital cohort study - Heidi Kruit; Saara Mertsalmi; Leena Rahkonen (BMC, 2022)
Abstract Background Finland has the world's highest incidence of 62.5/100000 of diabetes mellitus type 1 (DM1) with approximately 400 (1%) DM1 pregnancies annually. Pregnancies complicated by DM1 are accompanied with increased risk for perinatal morbidity and mortality. Timing and mode of delivery are based on the risk of complications, yet the data on labor induction is limited. The aim of this study was to compare delivery outcomes in planned vaginal (VD) and planned cesarean deliveries (CD) in late preterm and term DM1 pregnancies, and to evaluate the feasibility of labor induction. Materials and Methods Pregnant women with DM1, live singleton fetus in cephalic presentation ≥34 gestational weeks delivering in Helsinki University Hospital between January 1st 2017 and December 31st 2019 were included. The primary outcome were the rates of adverse maternal and perinatal outcome. The study population was classified according to the 1980-revised White's classification. Statistical analyses were performed by IBM SPSS Statistics for Windows. Results Two hundred four women were included, 59.8% (n = 122) had planned VD. The rate of adverse maternal outcome was 27.5% (n = 56), similar between the planned modes of delivery and White classes. The rate of perinatal adverse outcome was 38.7% (n = 79), higher in planned CD (52.4% vs. 29.5%;p = 0.001). The most common adverse perinatal event was respiratory distress (48.8% vs. 23.0%;p <  0.001). The rate of adverse perinatal outcome was higher in White class D + Vascular compared to B + C (45.0% vs. 25.0%, OR after adjustment by gestational age 2.34 [95% CI 1.20-4.50];p = 0.01). The total rate of CD was 63.7% (n = 130), and 39.3% (n = 48) in planned VD. Women with White class D + Vascular more often had emergency CD compared to White Class B + C (48.6% vs. 25.0%;p = 0.009). The rate of labor induction was 51%, being 85.2% in planned VD. The rate of VD in induced labor was 58.7% (n = 61) and the rate of failed induction was 14.1% (n = 15). Conclusion Planned VD was associated with lower rate of adverse perinatal outcome compared to planned CS, with no difference in the rates of adverse maternal outcome. Induction of labor may be feasible option but should be carefully considered in this high-risk population.